Determinants of the institutional isomorphism of the savings and credit cooperatives in Mexico - Lara Gómez, Graciela; Pérez Sosa, Felipe A. (REVESCO. Revista de Estudios Cooperativos, 2015)
The aim of this work is to establish whether the savings and credit cooperatives are isomorphic to the formal banking system in Mexico; because those entities have operated traditionally in an environment of informality, but lately some of them have moved toward the formalization as a result of the requirements imposed by regulatory bodies. To this end, the present study was carried out with a mixed methodological approach, in which the results obtained through qualitative techniques were confirmed with statistical inferences based on hypothesis testing. With the qualitative approach could be established that the managers of the savings and credit cooperatives in Mexico have focused their efforts on meeting the regulatory systems arising from 2001 ; and with the results of the statistical tests it was determined that: a) No evidence of isomorphism is detected in the amounts of total assets; b ) Isomorphism traits are found in total loans and total deposits. In addition, it could be observed evidence suggesting that in these topics, the degree of institutionalization of some cooperatives is higher than that of some banks; c) Finally, it was determined that the existing isomorphism in the default rate is presented in three different ranges, depending on the degree of institutionalization of the studied entities. In conclusion, it is expected that the savings and credit cooperatives in Mexico will continue to experience changes driven by regulation and the market, which will encourage that the mimetic isomorphism prevail among them.